The UK ME/CFS Biobank for biomedical research on Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Multiple Sclerosis - Lacerda, Eliana M. (Open J Bioresour, 2017)
The UK ME/CFS Biobank was launched in August 2011 following extensive consultation with professionals and patient representatives. The bioresource aims to enhance research on myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), related to pathophysiology, biomarkers and therapeutic approaches. The cohort includes 18–60 year olds, encompassing 284 clinically-confirmed ME/CFS cases, 60 neurologist-diagnosed multiple sclerosis (MS) cases, and 135 healthy individuals. The Biobank contains blood samples, aliquoted into serum, plasma, peripheral blood mononuclear cells (PBMC), red blood cells/granulocyte pellet, whole blood, and RNA (totalling 29,863 aliquots). Extensive dataset (700 clinical and socio-demographic variables/participant) enables comprehensive phenotyping. Potential reuse is conditional to ethical approval.